Coping With Limited Prosecutorial Resources: An Assessment of the Case Processing and Community Impact From the Perspective of Prosecutors and Staff in a Southeastern County - Metcalfe, Christi (Criminal justice policy review, 2023)
Counties across the country are experiencing population growth with associated crime increases while prosecutor offices remain under-resourced. Resource constraints have implications for case processing and community relations. This study offers a descriptive assessment of prosecutor and staff perceptions on resource challenges, using the Mecklenburg County District Attorney’s Office in North Carolina as a case study—a county where staffing and funding has stagnated over the past decade. Employing official data, interviews, and surveys, we considered how prosecutorial resources in Mecklenburg County compared with similar counties within the state, region, and country, as well as explored perceptions of resource constraints and the impact on office effectiveness and the community. Results suggested that Mecklenburg County did not compare favorably with similar counties in the region and nation, suffered more broadly from criminal justice funding challenges, and faced staffing shortages and turnover that were perceived as affecting case dispositions, office morale, and community trust.